2022
DOI: 10.3390/jdb10020024
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome Sequencing and Analysis of Differential Gene Expression among Various Stages of Tail Regeneration in Hemidactylus flaviviridis

Abstract: Across the animal kingdom, lizards are the only amniotes capable of regenerating their lost tail through epimorphosis. Of the many reptiles, the northern house gecko, Hemidactylus flaviviridis, is an excellent model system that is used for understanding the mechanism of epimorphic regeneration. A stage-specific transcriptome profile was generated in the current study following an autotomized tail with the HiSeq2500 platform. The reads obtained from de novo sequencing were filtered and high-quality reads were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…5 and 6) but proteomic analysis has been more limited. 7,8 RNA-Seq-based analysis has identified a number of common gene regulatory pathways involved in appendage regeneration, including the p38 MAPK and Wnt/Hippo signaling pathways. 5,9 The green anole lizard, Anolis carolinensis, was the first squamate and nonavian reptile to have its genome sequenced 10 and since then, there have been several transcriptomic studies analyzing the scar-free healing and regrowth phase of tail regeneration in this species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 and 6) but proteomic analysis has been more limited. 7,8 RNA-Seq-based analysis has identified a number of common gene regulatory pathways involved in appendage regeneration, including the p38 MAPK and Wnt/Hippo signaling pathways. 5,9 The green anole lizard, Anolis carolinensis, was the first squamate and nonavian reptile to have its genome sequenced 10 and since then, there have been several transcriptomic studies analyzing the scar-free healing and regrowth phase of tail regeneration in this species.…”
Section: Introductionmentioning
confidence: 99%
“…The green anole lizard, Anolis carolinensis , was the first squamate and nonavian reptile to have its genome sequenced 10 and since then, there have been several transcriptomic studies analyzing the scar‐free healing and regrowth phase of tail regeneration in this species 5,9,11–13 . In addition to A. carolinensis , transcriptomic studies on regrowth have been conducted in at least four other lizard species (Liu et al 2015, Vitulo et al 2017a, Vitulo et al 2017b, Patel et al 2022, Pawan et al 2019). Together, these studies indicate that the genes related to limb regrowth are relatively conserved across lizards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that such a remarkable regenerative power in the tail in lizards have evolved using an alternative sequence in genes activation with respect to that of the developing tail (Alibardi, 2020a). Transcriptomic and expression studies (Hutchins et al, 2014;Nagumantri et al, 2021;Patel et al, 2022;Ranadive et al, 2018;Vitulo et al, 2017aVitulo et al, , 2017bXu et al, 2020) have detected numerous oncogenes driving cell proliferation while others act as likely tumour suppressors leading to a regulated regeneration of a new tail (Alibardi, 2019). These studies have also indicated that the control of inflammation is essential for promoting tail regeneration and that the regenerating tail forms an immune-suppressive environment, like during amphibian and fish regeneration (He et al, 2021;Mescher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bl, blastema cells; cs, connective septum; mu, muscles; n, nucleus; sc, spinal cord; st, tail stump; w, wound (regenerating) epidermis [Colour figure can be viewed at wileyonlinelibrary.com] Blastema cells derive from various tissues after dedifferentiation or from local stem/progenitor cells that initiate proliferation as indicated from autoradiographic and immunolabelling studies (Alibardi, 2017a(Alibardi, , 2018Londono et al, 2017;Figure 1g). These studies have shown that some classical oncogenes such as c-myc, tel, wnts, eg and fgfrfr and their proteins, are activated in numerous small cells located among stump tissues and that successively accumulate to form the blastema (Hutchins et al, 2016;Alibardi, 2020;Patel et al, 2022;Figure 1h). Blastema cells are immersed in a hyaluronate-rich extracellular matrix present underneath a stratified wound (regenerating) epidermis (Figure 1i).…”
Section: Introductionmentioning
confidence: 99%